Spatial patterns in the microarthropod community associated with Azorella selago (Apiaceae) on the sub-Antarctic Prince Edward Islands - Hugo, Elizabeth Aletta (Stellenbosch : Stellenbosch University, 2006)
Dissertation (PhD)--University of Stellenbosch, 2006. ENGLISH ABSTRACT: The spatial distribution of animals and plants at different scales is a central theme in ecology. Knowledge of biodiversity distribution is essential, especially with the current threat of climate change and invasion by alien species. Since the impact of climate change and alien species will be, and has already been pronounced in polar regions, information on the current spatial distributions of biota in these regions is critical to predict the consequences of climate change and alien species on the future survival, distribution and abundance of indigenous biota. This study was conducted on the sub- Antarctic Prince Edward Islands (consisting of Marion Island and Prince Edward Island), which have experienced rapid climate changes over the past 50 years. Additionally, a number of alien plant, vertebrate and invertebrate (also microarthropod) species have been introduced to these islands. Since microarthropods (mites and springtails) play an essential role in decomposition and mineralization of plant material on the islands, the loss of microarthropods from decomposer communities might have disastrous results for ecosystem processes. Therefore it is essential to know the current distributions of microarthropods in order to predict future distributions patterns in reaction to climate change and invasive species. In this study, the spatial distribution of mites and springtails inhabiting the cushion plant Azorella selago Hook, were examined at different scales of observation. Firstly, the microarthropod community was examined at a fine scale. The relationship between microarthropod species richness and abundance and plant size, isolation, within-plant variability, grass cover and microclimate variables were investigated. Thereafter, the spatial variability of microarthropod abundances was examined within stands of plants, with statistical methods using varying degrees of locational information to determine if microarthropod abundance is ...